Leverage On Firm Value: The Role of Financial Performance Mechanisms - Rizqa Anita; Abdillah, Muhammad Rasyid; Suseno, Giri (School of Business, Bogor Agricultural University (SB-IPB), 2023)
During the COVID-19 pandemic, several companies increased their leverage to enhance their performance and ultimately impact the value of their firm. The purpose of this study is to investigate the relationship between leverage and firm value as well as to examine the potential mediating role of firm performance, specifically return on equity and earnings per share. The study employs a quantitative approach, utilizing the partial least squares-structural equation modeling (PLS-SEM) tool, with a sample of 687 companies listed on the Indonesia Stock Exchange (IDX) for the 2021 period. Sampling was conducted using a purposive sampling method. The findings indicate that leverage does not have a direct impact on firm value, but rather, the mediating role of return on equity is significant in this relationship. In contrast, earnings per share were found not mediate the relationship between leverage and firm value. This study provides an important contribution in the field of financial performance to managers and investors in making decisions. Limitations and suggestions for future research will be discussed. Keywords: decisions making, financial performance, firm value, indonesia stock exchange, leverage, structural equation modeling